Neonatal Resuscitation with Placental Circulation Intact - Pratesi, Simone; Hutchon, David; Katheria, Anup (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection of articles aims to promote the spread of a new way of resuscitating newborns in the delivery room: to perform exactly the same neonatal resuscitation procedures in a different landscape, that is, at mother's side with an intact cord.